Frequency of Faith and Spirituality Discussion in Health Care - Bergamo, David (Journal of religion and health, 2016)
Faith and spirituality are important in the lives of many individuals, and therefore, many patients. This study was performed to determine whether faith and spirituality are active part of the healthcare field and patients’ receipt of these sometimes delicate topics. The nuances of the concepts of faith, spirituality, and religion and their implications in the healthcare setting are discussed. Benefits and detriments of faith and spirituality are reviewed in terms of how they relate to the health of the patient and to the healthcare field. With the focus of healthcare shifting to holistic care, this conversation may be more necessary than ever in practice, yet it seems many providers are not discussing these matters with patients. The study analyzes whether healthcare providers are discussing these topics with patients and how the discussion is received or would be received by patients. Findings demonstrate the infrequency of the discussion regardless of the fact that the majority of patients consider themselves faithful or spiritual. This study was approved by the Clarkson University Institutional Review Board on June 18, 2104.